Félix Guattari`s schizoanalytic ecology - Berressem, Hanjo, 1956- (Edinburgh University Press, 2019)
Hanjo Berressem establishes the notion of a schizoanalytic ecology as the most consistent conceptual spine of Félix Guattari's work. He covers the whole range of Guattari's solo work and the books co-authored with Gilles Deleuze, primarily a rigorous explication and analysis of 'Schizoanalytic Cartographies'.